Association between tooth loss and cognitive performance: 11‐year follow‐up cohort study. (31st December 2021) - Asher, Sam; Stephen, Ruth; Ngandu, Tiia; Koskinen, Seppo; Suominen, Anna Liisa; Solomon, Alina
Abstract: Background: Emerging evidence suggests tooth loss to adversely affect cognition. This study assessed association between tooth count and cognitive performance over 11 years. Method: This study included 6537 participants (2933 males, 3604 females), aged 30‐99 years old (mean 53.4 years) from Finnish Health 2000 and 2011 Surveys. Tooth count was assessed clinically in 2000. Cognitive status was assessed either in 2000, 2011 or both, through battery of cognitive tests including Mini‐Mental Scale Examination (MMSE, short version, max 16‐points), Immediate word recall, Delayed word recall and Verbal Fluency (number of animals correctly listed). Cognitive tests were dichotomized according to median. Number of remaining teeth were categorized into 0, 1‐9, 10‐19 and ≥20. Logistic regression analyses were adjusted for age, gender, years of education, cardiovascular risk factors (FINRISK score), homocysteine, vitamin D and alcohol consumption. Result: In cross‐sectional analyses at baseline, lower tooth count was associated with lower cognitive tests scores. 10‐19 versus ≥20 teeth was associated with lower MMSE, and immediate and delayed recall scores. 1‐9 teeth was associated with lower MMSE score. Having 0 teeth was associated with lower MMSE and immediate recall scores. In longitudinal analysis significant associations were observed between 10‐19 teeth in 2000 and lower MMSE and immediate recall scores in 2011. No association was observed between tooth count and verbal fluency in either cross‐sectional or longitudinal analyses (Table 1). Similarly, no association was observed for tooth count and decline in any cognitive test score over 11 years. Conclusion: Preliminary results indicate that tooth loss may be linked to lower cognitive performance. Having 10‐19 versus ≥20 teeth appears to be particularly important. Individuals with 10‐19 teeth might have active or current periodontitis which could explain the observed associations. In contrast, individuals with low number of remaining teeth (0 or 1‐9) might not have periodontitis or lower burden of periodontal inflammation. The impact of periodontitis on cognition needs to be assessed in future studies. Acknowledgements: The authors wish to acknowledge Juho Vainio Foundation (Finland), Finnish Brain Foundation (Finland) & Päivikki and Sakari Sohlberg Foundation (Finland), Finnish Dental Society Apollonia and Finnish Dental Association.